The implementation of graphic motion-based communication technology material learning videos for 3rd grade elementary students - Hamidah, Azmi Fauziah; Firmansyah, Feri Hidayatullah; Permana, Fahmi Candra; Azizan, Ahamad Tarmizi (Universitas Negeri Yogyakarta, 2023)
Motion graphic-based learning videos are a digital learning medium that clarifies material, increases student learning independence, can be accessed quickly, and is not limited in time. This study aimed to determine the implementation and feasibility of motion graphic-based learning videos on the material 'Communication Technology' for third-grade students of Luqmanul Hakim Integrated Islamic Elementary School, Bandung City. This research uses the Design and Development (DD) model. This research went through five stages, namely (1) problem identification, (2) Determining goals and solutions, (3) Product design and development, (4) Trials, and (5) Communication. Data collection techniques used were interviews and questionnaires. Two experts are involved in this study: material and media experts. The sampling technique used is saturated sampling. Namely, the total number of grade 3 students is 24 students. The validation results by the material experts showed a percentage of 100% with the qualification